Studies on CYP3A activity during the menstrual cycle as measured by urinary 6β‐hydroxycortisol/cortisol - Helena Bergström; Anna Lindahl; Anna Warnqvist; Ulf Diczfalusy; Lena Ekström; Linda Björkhem‐Bergman (Wiley, 2021)
Abstract The 6β‐OH‐cortisol/cortisol ratio (6β‐OHC/C) in urine is an endogenous marker of drug‐metabolizing enzyme cytochrome P450 3A (CYP3A). The primary aim of this single center, prospective, non‐interventional cohort study, was to investigate the variability of 6β‐OHC/C during the menstrual cycle. In addition, possible associations between the CYP3A activity and sex hormones, gut microbiota metabolite trimethylamine‐N‐Oxide (TMAO) and microRNA‐27b, respectively, were investigated. Serum and urinary samples from healthy, regularly menstruating women followed for two menstrual cycles were analyzed. Twenty‐six complete menstrual cycles including follicular, ovulatory, and luteal phase were defined based on hormone analyses in serum. 6β‐OHC/C were analyzed in urine and sex hormones, TMAO and miRNA‐27b were analyzed in serum at the same time points. 6β‐OHC/C did not vary between the follicular, ovulatory, or luteal phases. There was a difference in the relative miRNA‐27b expression between the follicular and ovulatory phase (p = .03). A significant association was found between 6β‐OHC/C and progesterone during the follicular (p = .005) and ovulatory (p = .01) phases (n = 26 for each phase). In addition, a significant association was found between the ratio and TMAO during the ovulatory (p = .02) and luteal (p = .002) phases. 6β‐OHC/C and gut microbiota TMAO were significantly associated (p = .003) when evaluating all values, for all phases (n = 78). Interestingly, the finding of an association between 6β‐OHC/C in urine and levels of TMAO in serum suggest that gut microbiota may affect CYP3A activity.